Tnjauan Yuridis Tentang Peran Dan Kedudukan Komisi Aparatur Sipil Negara Ditinjau Dari Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara - Muklis Muklis (Iuris Studia: Jurnal Kajian Hukum, 2021)
The issuance of Law no. 5 of 2014 concerning the State Civil Apparatus (ASN) almost four years ago became a new episode in managing the government bureaucracy. As a product of public policy, the ASN Law was born due to the encouragement of a policy environment in the form of the still low performance of the bureaucratic apparatus and the high politicization of the bureaucracy so that the public's demands on him were increasing. For more than five decades since independence in 1945, its existence and work were like the small spare parts of a giant state machine whose direction of development was highly dependent on the political rulers at that time. Reflecting on the above statement, the State Civil Apparatus Commission was formed, hereinafter referred to as KASN, which in general has the task of supervising ASN employees. In the ASN Law, KASN is a non-structural institution that is independent and free from political intervention to create professional and performing ASN employees, provide fair and neutral services, and become the glue and unifier of the nation. This writing uses normative juridical legal research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of the role of the State Civil Service Commission. Sources of research data are in the form of primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. Related to the function of KASN, it is contained in Article 30 of Law No.5 of 2014 that "KASN has the function of supervising the implementation of basic norms, code of ethics and code of conduct of ASN, as well as the implementation of the Merit System in ASN policies and Management in Government Agencies". KASN is tasked with maintaining the neutrality of ASN employees, supervising the ASN professional development and, reporting the supervision and evaluation of the implementation of ASN Management policies to the President. The State Civil Apparatus Commission can recommend the president to impose sanctions on civil service officials and officials who violate the principles according to the provisions of the law. The forms of sanctions referred to above lie in Article 33 paragraph (2), namely Warning, Warning, Correction, revocation, cancellation, issuance of decisions, and / or refunds, Disciplinary penalties for Competent Officers in accordance with the provisions of laws and regulations, Sanctions for Civil Service Officer, in accordance with the provisions of laws and regulations